Recent research progress in PEM fuel cell electrocatalyst degradation and mitigation strategies. Issue 5 (September 2021) - Wei, Xin; Wang, Ru-Zhi; Zhao, Wei; Chen, Ge; Chai, Mao-Rong; Zhang, Lei; Zhang, Jiujun
Abstract: The performance degradation of proton exchange membrane fuel cells (PEMFCs) is one of the most critical challenges in their practical applications. Degradations of electrocatalysts for oxygen reduction reaction (ORR) at cathode and hydrogen oxidation reaction (HOR) at the anode are the major contributors to PEMFC degradation, which are mainly induced by fuel/air impurities, unintentional harmful species during the preparation and use of the catalysts, as well as catalyst decomposition during the operation. This review summarizes the recent research on PEMFC performance degradation and the progress in developing mitigation strategies for avoiding the degradation. Several aspects are emphasized as follows: the understanding of catalyst poisoning phenomena, influencing factors, and general degradation mechanisms. Several technical challenges are analyzed and the corresponding future research directions are proposed to facilitate the further research and development of mitigation strategies for PEMFC catalyst degradation. Graphical abstract: Image, graphical abstract